Enantioselective rhodium-catalyzed coupling of arylboronic acids, 1,3-enynes, and Imines by alkenyl-to-allyl 1,4-rhodium(I) migration - Callingham, Michael; Partridge, Benjamin M.; Lewis, William; Lam, Hon Wai (Wiley-VCH Verlag, 2017)
A chiral rhodium complex catalyzes the highly enantioselective coupling of arylboronic acids, 1,3-enynes, and imines to give homoallylic sulfamates. The key step is the generation of allylrhodium(I) species by alkenyl-to-allyl 1,4-rhodium(I) migration.